Money Politic and Political Offenses: Relationship Study and its Influence on Extradition in Indonesian Criminal Law - David Hardiago; Dey Ravena; Rusli K. Iskandar; Syafrinaldi; Rani Fadhila Syafrinaldi (International Conference On Law And Social Sciences, 2024)
The absence of normative boundaries for political offenses has led to the emergence of two main categories: money politics and mechanisms for extraditing the perpetrators of crimes. The initial camp that meets the criteria of being classified as a criminal act in money politics is a political crime, thereby suggesting that the individual responsible for this wrongdoing cannot be subjected to extradition. On the other hand, the second camp does not meet the criteria for being considered a criminal act. Money politics, which is classified as a political offense, implies that the offender could potentially face extradition. Nevertheless, this perspective presents an additional legal quandary in terms of determining its applicability across all cases of money politics. The objective of this research is to delve into this antinomy by placing emphasis on the primary issues at hand. These issues can be outlined as follows: Firstly, what is the correlation between criminal acts, money politics, and political offenses in the context of Indonesian criminal law? Secondly, what are the potential developments in the extradition process concerning criminal acts involving money politics in the future? This article will make use of normative legal research, employing a conceptual, statutory, case-based, historical, and comparative approach. This comprehensive study yields insightful conclusions. Firstly, it delves into the intricate relationship between political offenses and criminal acts within the realms of Indonesian criminal law. This exploration gives rise to two contrasting perspectives. On one hand, it defines criminal acts as an integral part of political offenses, whereas, on the other hand, it posits that criminal acts should not be classified as political offenses. Both viewpoints carry significant implications concerning the extradition process for individuals involved in money politics. Secondly, in anticipation of differing opinions, criteria for political offenses have been formulated as projections for the potential reformulation of the current extradition regulations, both partially and entirely.